BARRO, Jorge Henrique. Guia Prático de Missão Integral. Londrina: Editora Descoberta, 2013. 311 p. - Neto, Willibaldo Ruppenthal (Vox Scripturae - Revista Teológica Internacional, 2017)
BARRO, Jorge Henrique. Guia Prático de Missão Integral. Londrina: Editora Descoberta, 2013. 311 p.